MANAJEMEN AKHLAK DAN KARAKTER PENDIDIKAN ANAK USIA DINI - Anisa Putri (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
This study aims to determine the management of morals and character in early childhood. Many found various kinds of behavior that can determine the character of different early childhood. So, a rule is needed to minimize the attitudes and behavior of children in early childhood starting early, especially in the influence of this increasingly advanced era. Education is basically in the form of guiding and consciously teaching educators to students with regard to the physical and spiritual development of children so that the formation of a good and neat personality. This study measures all aspects of moral and character management, namely: positive and negative, the purpose of this study is also to find out how the influence of character education management on morals in early childhood. The method used is a quantitative method with research data with data analysis. Data collection techniques in the form of interviews (interviews) by way of one-sided question and answer which is carried out systematically and based on the research objectives. Sources of data in this study in the form of respondents and observations. Data collection techniques in the form of research reports. The results of this study indicate that students are also expected to be able to follow and make themselves effective in order to establish unity in education which will later be in the form of good morals in developing learning character.